ARC: ACTION RESEARCH NETWORKS FOR LANGUAGE TEACHERS - Christine Lechner; Marianne Jacquin (Babylonia, 2019)
Below, we present the Action Research Communities for Language Teachers (ARC) project, which was implemented at the European Centre for Foreign Languages (www.ecml.at) as part of the "Languages at the Centre of Learning" program.